Names forming and deforming identities: A psychoanalytic approach to Jhumpa Lahiri’s The Namesake - Mohammed, Ali; Berzenji, Latef (Al-Adab Journal, 2023)
The article studies the calamities the migrants face in western societies. It uses Frantz Fanon’s ideas of psychoanalysis to critically read and examine Jhumpa Lahiri’s novel The Namesake. The novel narrates the events that occurred to an Indian family abroad for thirty-two years from 1968 to 2000. The cultural clashes a newly arrived couple from Calcutta, India encounter in Cambridge, America to the calamities their children later face are meticulously depicted in the story. Most of the novel’s events revolve around Gogol Ganguli, who suffers from a duality of personality and develops double consciousness because of his Indian name. The study finds that although they distance themselves from their traditions and embrace the western culture, the migrants can not fully assimilate to the white culture and eventually develop identity crises.